The Role of Supply Chain Information Sharing on Business Performance: Case of Fashion Companies In Pekalongan, Indonesia - Kamilatunnuha, Ayu Hamida; Kusumawardhany, Prita Ayu; Andjani, Erna (Universitas Nahdlatul Ulama Surabaya, 2024)
The creative industry in Indonesia is currently experiencing very rapid development. One creative industry that always has high opportunities and potential is the fashion industry. The fashion industry can boost the economy and the fashion industry is one of the key factors in creative growth which covers 17 percent of the creative economy in Indonesia and has the potential to open job opportunities and increase income. This gives rise to intense competition between companies. Companies are trying to maintain their advantages to face increasingly competitive competition, especially in managing supply chains. In the industrial era 4.0, supply chain processes can be integrated optimally with lower costs and shorter implementation times in sharing information. This research aims to determine the effect of supply chain integration sharing, supply chain integration, operational performance, and business performance slot maxwin on the research object of fashion companies in Pekalongan. This research uses quantitative methods and uses SEM analysis using SPSS and AMOS software. This research sample consists of 150 respondents and has 4 variables. The results of this research show that supply chain information sharing has a positive effect on supply chain integration and operational performance. Supply Chain Information Sharing has no positive effect on business performance. Supply chain integration has a positive effect on business performance and operational performance. Operational performance has a positive effect on business performance.